Febrile seizures in Kaduna, north western Nigeria - Eseigbe, E. E. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Febrile seizure is the most common seizure of childhood and has a good prognosis. However its presentation is fraught with poor management, with grave consequences, in our environment. Thus a review of its current status is important. OBJECTIVE: To review the status of febrile seizures in Kaduna metropolis. MATERIALS AND METHODS: A review of cases seen in the Department of Paediatrics, 44 Nigeria Army Reference Hospital, Kaduna between June 2008 and June 2010. RESULTS: Out of the 635 cases admitted in the department 17 (2.7%) fulfilled the criteria for febrile seizures. There were 11 Males and 6 Females (M: F, 1.8:1). Age range was from 9 months to 5 years with a mean of 2.2 years ± 1.1 and peak age of 3 years. Twelve (70.6%) were in the upper social classes (I-III). Fever, convulsion, catarrh and cough were major presenting symptoms. Incidence of convulsion was least on the 1st day of complaint. Fourteen (82.4%) of the cases were simple febrile seizures while 3 were complex. There was a positive family history in 5 (29.4%) of the cases. Eleven (64.7%) had orthodox medication at home, before presentation, 5 (29.4%) consulted patient medicine sellers and 7 (41.7%) received traditional medication as part of home management. Malaria and acute respiratory infections were the identifiable causes. Standard anti-malaria and anti-biotic therapy were instituted, where indicated. All recovered and were discharged. CONCLUSION: There was a low prevalence of febrile seizures among the hospitalized children and a poor pre-hospitalization management of cases. It highlighted the need for improved community awareness on the prevention and management of febrile seizures.